2007
DOI: 10.1097/01.ccm.0000275273.56547.b8
|View full text |Cite
|
Sign up to set email alerts
|

Soluble vascular endothelial growth factor receptor-1 protects mice in sepsis

Abstract: These findings support a critical protective role of sFlt-1 in endotoxic shock and sepsis. sFlt-1 may therefore have utility as an adjunctive agent for the treatment of sepsis syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 43 publications
4
53
1
3
Order By: Relevance
“…These characteristics make sFlt-1 function as a dominant-negative inhibitor against VEGF and PlGF. 17,22 Serum sFlt-1 has been reported to be an antiangiogenesis factor that can inhibit tumor growth and metastasis. 23 According to our results, the preoperative serum sFlt-1 was decreased in the serum of CRC patients, compared with the levels of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics make sFlt-1 function as a dominant-negative inhibitor against VEGF and PlGF. 17,22 Serum sFlt-1 has been reported to be an antiangiogenesis factor that can inhibit tumor growth and metastasis. 23 According to our results, the preoperative serum sFlt-1 was decreased in the serum of CRC patients, compared with the levels of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Large retrospective cohort studies have documented a 3-to 7-fold increased risk of developing cardiovascular disease in women with preeclampsia later in life [28]. This increased risk is based on genetic determinants shared with metabolic syndrome and inflammation [29].…”
Section: Insulin Resistance In Preeclampsia and Resultant Endothelialmentioning
confidence: 99%
“…In addition, Shapiro et al [9] showed that the circulatory soluble fms-like tyrosine kinase-1 receptor (sFlt-1) level was increased in septic patients and that the increase was correlated with disease severity. Furthermore, our group [11] and Yano et al [12] have demonstrated that treatment with exogenous sFlt-1 or adenovirus-mediated overexpression of sFlt-1 attenuates inflammatory response and decreases mortality in experimental sepsis through antagonization of LPS-induced VEGF secretion [11,12]. These findings indicate that increasing the plasma sFlt-1:VEGF ratio during sepsis may be an effective therapeutic adjuvant for treatment of septic shock as well as severe immune responses caused by microbe-mediated diseases.…”
Section: Introductionmentioning
confidence: 90%